Trends and patterns of exclusive breastfeeding for under-6-month-old children - Parizoto, Giuliana M.; Parada, Cristina Maria Garcia de Lima [UNESP]; Venancio, Sonia I.; Carvalhaes, Maria Antonieta de Barros Leite [UNESP] (Sociedade Brasileira de Pediatria, 2009)
Objective: To study the trends and patterns of exclusive breastfeeding (EBF) for under-6-month-old infants in the city of Bauru, southeastern Brazil.Methods: We compared data from three cross-sectional surveys, using similar methodologies, which were part of a project for monitoring breastfeeding indicators in the state of São Paulo, Brazil. The sample included infants aged 0 to 6 months who attended one of the two rounds of the nationwide infant vaccination campaign in 1999, 2003 and 2006 (respectively: 496, 674 and 509 infants). Descriptive statistics were used to compare the prevalence of EBF according to age (in months) and group of children under 6 months of age. Differences in prevalence were expressed as percentage-points and submitted to statistical analysis (Pearson's chi-square and tendency), and the level of significance was set at p < 0.05. Factors associated with EBF interruption in 2006 were evaluated by univariate and multivariate analyses.Results: An increase in the prevalence of EBF was observed in under-6-month-old infants: 1999-2003, increase of 9.1 percentage-points; 2003-2006, increase of 6.6 percentage-points, resulting in an annual increase rate of 2.3 percentage-points for the first period and 2.2 percentage-points for the second period. Significant inverse association was observed between EBF and the use of pacifiers (prevalence ratio = 2.03; 95% confidence interval 1.44-2.84).Conclusion: EBF prevalence in under-6-month-old infants in the city of Bauru, southeastern Brazil, increased almost threefold over the period studied, from 8.5% in 1999 to 24.2% in 2006, a total increase of 184.7%. The use of pacifiers was the only factor strongly associated with the interruption of EBF.
Keywords: Breastfeeding; epidemiology; cross-sectional studies; child nutrition; human milk